(5-n-Heptyl-2-hydroxymethyl-1,3-dioxan-2-yl)methanol - Yuan, Xian-You; Zhang, M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C13H26O4, the dioxane rings adopts a chair conformation; the n-heptyl chain occupies an equatorial position. In the crystal, molecules are connected by O-H center dot center dot center dot O hydrogen bonds into a zigzag chain running along the a axis, giving rise to a herringbone pattern. There are two independent molecules in the asymmetric unit.